Gender differences in visual mathematical thinking: A case study on algebra problem solving and e-learning integration using edlink - Fitriawan, Dona; Siregar, Nurfadilah; Rif’at, Mohammad (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This research aims to 1) analyze gender-based differences in visual mathematical thinking for solving algebraic problems, 2) explore how e-learning technology, specifically the Edlink platform, supports algebra understanding through visualization, and 3) assess the effectiveness of mathematical software in aiding students to visualize and solve algebraic problems. Method: A qualitative approach with a descriptive-exploratory method was used for this study. It involved a case study of students enrolled in the Mathematics Education Program who attended algebra courses. Data were collected through tests, questionnaires, interviews, direct observation, and documentation. The study sample consisted of 278 students, including 98 male and 180 female participants. Descriptive statistics and independent samples t-tests were employed to analyze the gender-based differences in visual thinking abilities. Findings: The results indicate that male students demonstrated more dominant visual mathematical thinking abilities compared to female students, particularly in understanding, imagining, and presenting algebraic solutions. Statistically, the independent samples t-test revealed a significant gender difference (p < 0.001). The use of the Edlink e-learning platform was found to be effective in aiding students' algebra understanding through enhanced visualization of mathematical concepts. Significance: The study concludes that gender differences affect visual mathematical thinking abilities, with male students showing greater proficiency in solving algebraic problems visually than female students. Furthermore, the integration of the Edlink e-learning platform significantly enhanced students' understanding of algebraic concepts through effective visualization. Therefore, incorporating technology in mathematics education can enrich the learning experience and improve student outcomes.